Simulasi CFD Distribusi Temperatur pada Pengering Biji Kopi dengan Sistem Konveksi Paksa - Pasaribu, Humisar; Lumbangaol, Partahi; Napitupulu, Richard A.M; Siagian, Parulian; Siagian, Horas S; Setyawan, Eko Yohanes (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2023)
Drying is a mass transfer and heat transfer process that is strongly influenced by temperature and air velocity. The importance of analyzing the temperature distribution and air velocity is expected to be used as a reference to optimize the drying process to be faster and better. This study aims to analyze the temperature distribution and air velocity that occurs in a coffee bean dryer with a forced convection system using CFD simulation. CFD simulations are carried out using ANSYS Fluent software. with steady conditions, and using a pressure-based solver method. The obtained temperature distribution occurs with an estimated absorber temperature difference with the drying chamber is 31% during the day.